In vivo immunoregulatory properties of the novel mitochondria-targeted antioxidant SkQ1 - Yang, Yuhui; Karakhanova, Svetlana; Soltek, Sabine; Werner, Jens; Bazhin, Alexandr V. (Molecular immunology, 2012)
Reactive oxygen species (ROS) is a group of highly reactive oxygen-containing chemicals. ROS are essential for various biological functions, including cell survival and growth, proliferation and differentiation. At the same time ROS production is connected to a number of disorders, such as chronic inflammation, age-related diseases and cancers. In the immune system, ROS are involved in the defence of the host organism, immune response and immune regulation. One of the main sites of ROS generation in the cell is mitochondrial electron transport. In contrast to a number of traditional antioxidants, the novel mitochondria-targeted antioxidant SkQ1 exerts its antioxidant properties even in nanomolar concentrations. In this work, we investigated immunomodulatory properties of SkQ1 and demonstrated that treatment of mice with SkQ1 led to a decrease in percentage of CD8+ T cells but not of CD4+ T cells. We documented a decrease of a relative number of naïve T cells with a simultaneous increase in percentage of effector memory T cells. Central memory T cells had also a trend to be increased after SkQ1 treatment. In fraction of dendritic cells, we found an increase in percentage of plasmacytoid dendritic cells. In the case of myeloid cells, SkQ1 treatment decreased significantly the percentage of granulocytes. No effect of SkQ1 was observed on regulatory T cells, natural killer cells, natural killer T cells, as well as on freshly isolated CD8+ T or CD4+ T cells, indicating the indirect influence of SkQ1 on immune cells.